(untitled) (Architecture Image Studies, 2026)
This study sought to understand the factors that influence the perception of the extent of tax evasion in the service industry from the viewpoint of income and sales tax auditors. In attempting the study objectives, the study based itself on the descriptive and analytical methods. The population of the study consisted of the auditors of the Income Tax Department of Jordan, of which the auditors in the General Directorate of Administration in Amman are 290. A random sample of 172 participants was chosen, and their responses to electronically distributed questionnaires were analyzed. Several statistical methods were utilized to process the data. The study concluded with the presence of the factors affecting tax evasion (legal, technological, ethical, and organizational) and the role they play in tax evasion in the service industry from the perspective of income and sales tax auditors. The study recommended establishing tax legislation that is more stringent to eliminate loopholes and increase punishments.